ASSOCIATION OF NOS3 GENE POLYMORPHISM rs1799983 WITH IN-STENT RESTENOSIS OF CORONARY ARTERIES - Zimbakov, Zan; Busljetik, Oliver; Jovanova, Silvana (Journal of Morphological Sciences, 2022)
Revascularization by percutaneous coronary intervention (PCI) with stent implantation is an invasive technique commonly used in the therapy of acute coronary syndromes, including the myocardial infarction and other types of ischemic coronary disease. Although it is highly effective, some patients develop an in-stent restenosis requiring repeat percutaneous revascularization. Recent studies have indicated genetic association of single nucleotide polymorphisms in certain genes with the risk of restenosis. The aim of this study was to investigate the association of NOS3 gene rs1799983 (Glu298Asp) polymorphism with the in-stent restenosis of implanted coronary stents. In this prospective, observational, genetic-associated, case-control study demographic, clinical and laboratory data were analyzed from preliminary selected group of 77 patients with implanted coronary stents, of which 46 were with in-stent restenosis and 31 without restenosis. The gender and age distributions were similar among the two patient groups. Using different genetic models, genetic association of NOS3 gene rs1799983 polymorphism and in-stent restenosis was revealed ( p <0.05). Restenosis odds ratio indicated the protective role of the dominant G allele, while the minor variant T allele was associated with an increased risk of in-stent restenosis. Keywords : in-stent restenosis, coronary stent, polymorphism gene, NOS3. https://doi.org/10.55302/JMS2251096z